2022
DOI: 10.3390/lubricants11010011
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Lubrication and Antioxidation Efficacies of Graphene Oxide and Fullerenol as Biological Lubricant Additives for Artificial Joints

Abstract: The service life of artificial joints has gradually failed to meet the needs of patients. Herein, the synergistic lubrication and antioxidant efficacies of graphene oxide (GO) and fullerenol (Fol) as biological lubricant additives for artificial joints were investigated. The lubrication mechanisms of biological lubricant containing GO and Fol at the friction interface of artificial joints were then revealed. Tribological tests showed that the average friction coefficients of Al2O3–Ti6Al4V pairs and Ti6Al4V–UHM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Furthermore, the results show that the DIG, GO, and Fe 3 O 4 MNPs synergistically interact in terms of their ability to free radicals scavenging. This phenomenon can be attributed to the tendency of spherical Fe 3 O 4 MNPs and lamellar GO to aggregate into significant clusters in aqueous solutions, thereby impeding their capability to effectively scavenge radicals [ 61 ]. When both DIG/GO/Fe 3 O 4 nanocomposite were instantaneously exist in an aqueous solution, the spherical Fe 3 O 4 MNPs might be successfully loaded onto the GO lamellae and intercalated to reduce agglomeration.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the results show that the DIG, GO, and Fe 3 O 4 MNPs synergistically interact in terms of their ability to free radicals scavenging. This phenomenon can be attributed to the tendency of spherical Fe 3 O 4 MNPs and lamellar GO to aggregate into significant clusters in aqueous solutions, thereby impeding their capability to effectively scavenge radicals [ 61 ]. When both DIG/GO/Fe 3 O 4 nanocomposite were instantaneously exist in an aqueous solution, the spherical Fe 3 O 4 MNPs might be successfully loaded onto the GO lamellae and intercalated to reduce agglomeration.…”
Section: Resultsmentioning
confidence: 99%
“…In the past few decades, various new two-dimensional materials, including MXenes [6,7], MoS 2 [8,9], WS 2 [10], as well as graphene [11], have become a hot topic in the field of friction [12]. Among them, graphene has been widely considered by researchers due to its low surface energy and unique tribological properties [13][14][15] caused by easy-sliding multi-layer structures [16]. Omrani et al [17] modified graphene using oleic acid and found that 0.02 wt.% oleic acid-modified graphene could be well-dispersed in PAO9 and improve the friction-reducing and anti-wear properties effectively.…”
Section: Introductionmentioning
confidence: 99%